Modelo lei de escala para votos brancos e nulos em eleições estaduais brasileiras - Afonso, Luiz Henrique Dias (2021)
This study aimed at investigating the results of second rounds of the elections for governors of Brazilian states. To fully understand the voters' opinions, in a scenario of only two candidates, considering that white and null votes represent dissatisfaction with the options available candidates, these votes were considered the third option of the voters' opinion. Initially, the relations between the attendance and the votes were constructed for each of the three voting options, the two candidates and white and null votes, by city, separately, all modelled by scale laws. The relations for the two candidates were well adjusted together, allowing to obtain a single parameter model for these data, whereas the relations between whites and nulls were adjusted separately. Relationships for whites and nulls showed super linear scales in 70% of the elections, indicating that larger constituencies demand more. Using these results and conserving the probability of the attendance between the three voting partitions, a generalized and robust model of a single parameter was obtained by modelling white and null votes according to the attendance.